2020
DOI: 10.2147/dddt.s251623
|View full text |Cite
|
Sign up to set email alerts
|

<p>Epigallocatechin-3-Gallate Protects H<sub>2</sub>O<sub>2</sub>-Induced Nucleus Pulposus Cell Apoptosis and Inflammation by Inhibiting cGAS/Sting/NLRP3 Activation</p>

Abstract: Background: Intervertebral disc degeneration (IDD) is the most common diagnosis of patients with lower back pain. IDD is the underlying lesion of many spinal degenerative diseases; however, the role of cGAS/Sting/NLRP3 pathway and epigallocatechin gallate (EGCG) in the development of IDD remained unclear. Methods: The expressions of cGAS, Sting and NLRP3 mRNA of intervertebral disc (IVD) samples from IDD patients and controls were detected by RT-PCR. The nucleus pulposus cells (NPCs) were induced by hydrogen p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 40 publications
2
41
0
Order By: Relevance
“… 44 Previous studies demonstrated that LPS can induce the production of several inflammatory cytokines by activating the cGAS/STING signalling pathway 25 and that inflammatory responses activated by the cGAS/STING signalling pathway can in turn induce IVDD. 45 In this study, we found that cGAS/STING signalling pathway activated by LPS is closely related to IVDD. Figure 10 shows the activation of the cGAS/STING signalling pathway in the VI‐IVDD model and identifies this molecular cascade as the potential mechanism inducing IVDD (Figure 10D ).…”
Section: Discussionmentioning
confidence: 58%
“… 44 Previous studies demonstrated that LPS can induce the production of several inflammatory cytokines by activating the cGAS/STING signalling pathway 25 and that inflammatory responses activated by the cGAS/STING signalling pathway can in turn induce IVDD. 45 In this study, we found that cGAS/STING signalling pathway activated by LPS is closely related to IVDD. Figure 10 shows the activation of the cGAS/STING signalling pathway in the VI‐IVDD model and identifies this molecular cascade as the potential mechanism inducing IVDD (Figure 10D ).…”
Section: Discussionmentioning
confidence: 58%
“…Previous studies has been investigated the effect of EGCG on the oxidative stress and inflammatory response in intervertebral disc in animal model and in vitro cell culture. One study has provided results that EGCG treatment demonstrated significant protective effects in cell viability, apoptosis, cell cycle arrest and inflammatory status under oxidative stress through down-regulation of cGAS/Sting/NLRP3 pathway ( Tian et al, 2020 ). Findings from another study suggest that EGCG significantly inhibited the expression of pro-inflammatory mediators and matrix metalloproteinases in vitro , as well as radiculopathic pain in vivo , most probably by modulation of the activity of IRAK-1 and its downstream effectors p38, JNK and NF-κB ( Krupkova et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that EGCG inhibits IDD through multiple signaling pathways ( Krupkova et al, 2014 ; Tian et al, 2020 ). In our study, we propose the hypothesis that whether circadian clock-associated mechanisms play a role in preventive effects of EGCG against IDD.…”
Section: Introductionmentioning
confidence: 99%
“…Pigallocatechin-3-gallate is another natural polyphenol of green tea [ 83 ]. Tian et al [ 84 ] reported that IDD was associated with upregulation of cGAS, STING, and NLRP3; moreover, pigallocatechin-3-gallate inhibited the cGAS/STING/NLRP3 pathway and exerted antiapoptotic and anti-inflammatory effects. Gallic acid is a natural phenolic (a secondary metabolite of grape seeds, Syzygium fruticosum fruit, and other plants [ 85 ]).…”
Section: Natural Pharmacological Productsmentioning
confidence: 99%